Lingkungan Pengendapan Batugamping Daerah Oluhuta-Olele Kabupaten Bone Bolango Berdasarkan Karakteristik Mikrofasies - Mane, Moh Sajandri; Permana, Aang Panji; Hutagalung, Ronal; Aris, Ayub Pratama (Universitas Negeri Gorontalo, 2024)
Gorontalo has two types of limestone, namely reef limestone and clastic limestone. The research area has several formation units, such as Tinombo, Bilungala, Bone Diorite, Pinogu Volcano, and reef limestone. This research produces an analysis of the limestone depositional environment based on microfacies characteristics, as well as identifying the age of the limestone in the area. This research focuses on the Oluhuta and Olele areas in Bone Bolango Regency. Limestone, as the main focus, is a sedimentary rock with calcium carbonate as the main element. The constituent components involve granules, matrix and cement. Microfacies, the study of rock properties through thin sections, helps identify biological and mineral composition and interpret limestone qualities. The depositional environment of carbonate rocks is determined based on component abundance, grain shape, matrix origin, cement type, and rock packing. The methods used are petrography and micropaleontology. The results of research in the Olohuta - Olele area show that the geological conditions include geomorphological units of alluvial plains, coral reef plains and pyroclastic flow hills. The study area consists of Rudstone facies. Based on petrographic analysis, the research area is included in SMF-5, formed in the FZ-4 environment. Based on micropalentological analysis, the Rudstone Facies is aged N12 – N15 (middle Miocene – late Miocene).